Spontaneous Rupture of Superficial Femoral Artery Treated Endovascularly Using CO2 Angiography - Padhi, Rasmiranjan; Dhanasekaran, Jagadeesan; P., Vinoth (Journal of Clinical Interventional Radiology ISVIR, 2024)
Spontaneous rupture of the superficial femoral artery (SFA) is extremely rare. We report an interesting case of an elderly man presented with a history of hearing a click sound in his left lower thigh followed by sudden onset pain, swelling, and discoloration in the left lower limb while coming back from the bathroom. He was a known case of chronic kidney disease, and cirrhosis of the liver with moderate left ventricular (LV) dysfunction. We treated the ruptured SFA using overlapping stent grafts with CO2 angiography. The pseudoaneurysm got thrombosed. The pain and swelling of the left lower limb gradually subsided. The patient went home walking.
Keywords: spontaneous rupture of superficial femoral artery; stent graft; carbon dioxide angiography